TASKS AND SPESIFIC FEATURES OF NARRATING OBJECTS IN EXCURSION SERVICES IN THE TOURISM - Mirzayeva Lola Shermat qizi (XALQARO ILMIY-AMALIY ANJUMAN "TA’LIM MAYDONI TENDENSIYALARI: KOMPETENTSIYALAR, INNOVATSIYALAR VA TEXNOLOGIYALAR", 2025)
The important chores and special qualities of narrating items during excursion services in the tourism sector are discussed in this paper. It looks at how well good storytelling improves travel experiences, the difficulties tour guides have, and the methods used to produce interesting and educational stories. Combining literary evaluation, qualitative interviews with seasoned tour guides, and quantitative visitor surveys, the study employs a mixed-methods approach. The results underline the need of changing stories to fit different audiences, mixing factual knowledge with narrative, and using several approaches to keep visitors interested. This study advances knowledge of successful communication techniques in tourism and offers useful information to help excursion services be better.